2004
DOI: 10.1051/vetres:2004014
|View full text |Cite
|
Sign up to set email alerts
|

Routes of transmission and consequences of small ruminant lentiviruses (SRLVs) infection and eradication schemes

Abstract: -Small ruminant lentiviruses (SRLV = maedi-visna in sheep and caprine arthritis encephalitis in goats) are distributed throughout most countries of the world, particularly Europe. Laboratories from 16 European countries established collaborations within the framework of a COST (CO-operation in the field of Scientific and Technical Research) action sponsored by the European Union in order to (i) better organize their research programmes on SRLVs and (ii) to coordinate efforts to combat these two diseases. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
241
0
36

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 271 publications
(286 citation statements)
references
References 114 publications
9
241
0
36
Order By: Relevance
“…Maedi-Visna Virus (MVV) and the closely related Caprine Arthritis Encephalitis virus (CAEV) are grouped as Small Ruminant Lentiviruses (SRLV) be- [21,24]). Viral tissue tropism depends on the infecting strain and on the host's genetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maedi-Visna Virus (MVV) and the closely related Caprine Arthritis Encephalitis virus (CAEV) are grouped as Small Ruminant Lentiviruses (SRLV) be- [21,24]). Viral tissue tropism depends on the infecting strain and on the host's genetics.…”
Section: Introductionmentioning
confidence: 99%
“…The limited knowledge on the mechanisms of MVV-transmission between sheep contrasts with the numerous seroprevalence studies of Maedi-Visna worldwide [14,24], indicating that MVV has been reported from most major sheep producing countries except Australia and New Zealand [12]. Several studies have shown some evidence of breed associated susceptibility or resistance to MVV-infection and disease [8,9,13,23,31].…”
Section: Introductionmentioning
confidence: 99%
“…In the sheep mammary gland, little is known on the location and replication of MVV although tissue macrophages have been proposed to be the cells harbouring the virus and responsible for the presence of MVV in milk [8,19,36]. However, ovine mammary epithelial cells (OMEC) can be CAEV targets, at least in vitro [20].…”
Section: Introductionmentioning
confidence: 99%
“…This virus can lead to sub-clinical inflammation in one or more organs, mainly affecting the joints, nervous system, mammary glands, and respiratory system (BLACKLAWS et al, 2004). Caprine arthritis encephalitis (CAE) has been recorded worldwide (PETERHANS et al, 2004), is mainly found in dairy herds, and has been correlated with economic losses (ANDRIOLI et al, 2006). It is primarily transmitted to newborns via the colostrum; transmission can also occur via aerosol, animal-to-animal contact, and mating (PETERHANS et al, 2004;LE JAN et al, 2005).…”
Section: Introductionmentioning
confidence: 99%